AN ANALYSIS OF INDONESIA ENGLISH CODE MIXING IN FACEBOOK STATUS USERS - Yulianti Octavia Aurima; Windyawati Windyawati (IKIP Siliwangi, 2018)
This research investigates the use of code mixing in Facebook by Indonesian people. The purpose of this study is to describe the kind of code mixing used by Indonesian people in Facebook status users. This research employs the descriptive qualitative method. The data were taken from the Indonesian Facebook users posting. The data are analyzed based on Suwito’s theory. The results show that there are six types of linguistic forms of code mixing consisting of 11 data or 22% form of word; 21 data or 42% data phrase; 2 data or 4% repetition; 6 data or 12% idiom; 9 data or 18% clause; 1 data or 2% hybrid. Thus, the conclusion of this research is the students use two languages i.e. Indonesia and English as code mixing, and the researchers found the Facebook status users used code mixing of the phrase in the most form of code mixing. Keywords: Sociolinguistic, Code Mixing, Facebook